Additive manufacturing of lightweight and high-strength polymer-derived SiOC ceramics. Issue 2 (2nd April 2020) - Li, Ziyong; Chen, Zhangwei; Liu, Jian; Fu, Yuelong; Liu, Changyong; Wang, Pei; Jiang, Mingguang; Lao, Changshi
ABSTRACT: Lightweight and high-strength polymer-derived SiOC ceramics with varied lattice structures have been successfully produced using different polysiloxanes as preceramic polymers (PCPs) via photopolymerisation-based digital-light-processing 3D printing and pyrolysis. Photocurable precursor resins were prepared by simple mixing of polysiloxanes with photosensitive acrylate monomers, achieving good flowability and preserving desirable stability under different heating and oscillation conditions. Complex micron-sized structures were manufactured with high precision via the optimisation of polymer formula and printing parameters. The printed PCPs pyrolysed at 600–1000°C preserved fine features with uniform shrinkage. The skeletons were almost fully dense, with smooth and flawless surfaces at macro/micro scale. Porosities and mechanical properties, including apparent compressive strength, elastic modulus, and indentation hardness, were characterised. XRD, FT-IR, Raman spectroscopy, and XPS were used to explore the chemical variations in elements and atomic bonds. High specific compressive strength to density ratios was obtained for the SiOC lattices compared with other porous ceramics.